Vertical integration, separation in the rail industry: a survey of empirical studies on efficiency - Abbott, Malcolm; Cohen, Bruce (European Journal of Transport and Infrastructure Research, 2017)
Whether vertical separation of the rail industry creates demonstrable performance and efficiency gains is an issue of ongoing economic analysis and public policy debate. To assist in consideration of the merits and disbenefits of vertical separation this paper provides a summary of the different studies that have been undertaken to gauge the effects of vertical separation on the rail industry, and analyses and codifies the main findings of this research. The evidence indicates that whether separation will improve efficiency of a jurisdiction’s rail industry, and the extent to which this will occur, depends upon a number of specific conditions including what range of services are being provided – that is, passenger and/or bulk or general freight –the intensity of track use, and the extent to which inter-modal competition exists. The research highlights the merits of undertaking preliminary analysis of the characteristics of a jurisdiction’s rail sector before initiating structural reform of this nature.